EVALUATION OF THE EFFECTIVENESS OF AQUEOUS AND ALCOHOLIC EXTRACTS OF WORMWOOD AGAINST MULTIPLE ANTIBIOTIC-RESISTANT BACTERIA ACINETOBACTER BAUMANNII (CAHIERS MAGELLANES-NS, 2024)
Acinetobacter baumannii is a Gram-negative, multidrug-resistant (MDR) pathogen that causes nosocomial infections, especially in intensive care units (ICUs) and immunocompromised patients. A. baumannii has developed a wide range of antimicrobial resistance, associated with a higher mortality rate among infected patients compared to other non-baumannii species. In terms of clinical impact, resistant strains are associated with increases in both length of hospital stay and mortality. A. baumannii can cause a variety of infections, especially ventilator-associated pneumonia, bacteremia, and skin wound infections, among others. The most common risk factors for acquiring MDR A. baumannii are prior use of antibiotics, mechanical ventilation, length of ICU stay and hospital stay, severity of illness, and use of medical devices. Current efforts are focused on addressing all described antimicrobial resistance mechanisms in A. baumannii, with the aim of identifying the most promising therapeutic scheme. Plant extracts were used, represented by the wormwood plant, which proved effective in the current study against the bacteria under study that are resistant to multiple antibiotics.